Acceptability and adherence to a Mediterranean diet in the postnatal period to prevent type 2 diabetes in women with gestational diabetes in the UK: a protocol for a single-arm feasibility study (MERIT) - Doris Lanz; Julie Dodds; Graham Hitman; Elena Pizzo; Shakila Thangaratinam; Angeliki Bolou; Zoe Drymoussi; Francisco Jose Gonzalez Carreras; Maria del Carmen Pardo Llorente; Amy Thomas; James Heighway; Anita Sanghi; et al. (BMJ Open, 2021)
Introduction Women with gestational diabetes are at increased risk of developing type 2 diabetes later in life. In at-risk general populations, Mediterranean-style diet helps prevent type 2 diabetes. But its effect on postnatal women with a history of gestational diabetes is not known. Prior to a full-scale trial on Mediterranean-style diet in the postnatal period to prevent type 2 diabetes, a feasibility study is required to assess the acceptability of the diet and evaluate the trial processes.Methods and analysis MEditerranean diet for pReventIon of type 2 diabeTes is a single-arm feasibility study (65 women) with qualitative evaluation of women who have recently given birth and had gestational diabetes. The intervention is a Mediterranean-style diet supplemented with nuts and olive oil, with dietary advice and an action plan. A dedicated Health Coach will interact with participants through an interactive lifestyle App. Women will follow the intervention from 6 to 13 weeks post partum until 1 year post partum. The primary outcomes are rates of recruitment, follow-up, adherence and attrition. The secondary outcomes are maternal dysglycaemia, cost and quality of life outcomes, and acceptability of the intervention to participants, and to healthcare professionals delivering the intervention. Feasibility outcomes will be reported using descriptive statistics.Ethics and dissemination Ethical approval was obtained through the South Central—Berkshire Research Ethics Committee (19/SC/0064). Study findings will be disseminated via publication in peer-reviewed journals, as well as via newsletters made available to participants and members of Katie’s Team (a women’s health patient and public advisory group).Trial registration number ISRCTN40582975.